La inoculación ectomicorricica en plántulas de vivero en Costa Rica (ING) - Chaverri Polini, Adelaida (1991)
Mycorrhizae play an  important role in plant growth, since their prescence increases nutrient absorption, enhances resistance to adverse environmental factors, protects the rools from pathogens, and increases height and stem growth.Thirteen tree nursery administrators were interviewed in order to find out about ectomycorrhizal practices used. About 69.2% of the nurseries inoculate with Pisolithus tinctorius fruiting bodies, 15.4% use soil from pine plantations, and 7.8% use both methods. Tree nursery administrators lack sufficient knowledge about the function of ectomycorrhizae and the most effective inoculation methodologies.Furthermore, an experiment on ectomycorrhizal inoculation of oak seedlings was carried out. Three soil types and three treatments (inoculation with soil and roots from an oak forest, soil sterilization with methyl bromide and chloropicrine, and no treatment as control) were used. Results indicated that seedlings growing in inoculated soil showed most growth in stem height and larger stem dry weight. However, root dry weight of inoculated seedlings was less that those corresponding to seedlings growing in sterilized and control soil. This also demonstrates the effectivity of inoculation with oak forest soil.